Understanding children's mathematical graphics : beginnings in play - Carruthers, Elizabeth (New York : Open University Press, 2011)
This book challenges traditional beliefs and practices of teaching 'written' mathematics in early childhood. It gives a theoretical underpinning and offers exciting insights and context to children's early mathematical thinking and in particular their mathematical graphics.
Chapter1. Play and mathematics -- Chapter2. Beginnings in play -- Chapter3.Drawing, writing and maps -- Chapter4. Graphical signs: contexts and meanings -- Chapter5. Babies, toddlers and two-year olds -- Chapter6. Children's mathematical graphics -- Chapter7. Children's mathematical graphics in play -- Chapter8. Children's mathematical graphics in small group contexts -- Chapter9. Solving problems: children's mathematical graphics -- Chapter10.Children's voices -- Chapter11. Pedagogy that supports mathematical play -- Chapter12.Continuity and high expectations .
Includes bibliographical references and index.
Keywords: MATHEMATICS -- CHILDREN; EDUCATION -- TEACHING METHOD